Upaya Meningkatkan Nilai 8 Standar Nasional Pendidikan Akreditasi Sekolah melalui Supervisi Pembimbingan Terpadu pada Madrasah Ibtidaiyah di Kabupaten Sleman - Sri Wahyuni (Jurnal Pendidikan Madrasah, 2018)
This research method using action research supervision, namely providing action against madrasa or teacher in charge as the team successful accreditation of the school/madrasa. Action of supervision consists of two cycles, each cycle includes: planning, implementation, observation/observation and reflection. I cycle on physical evidence that has been filled with good and right on MI Al Islam 32.48%, at MI Al Ihsan there 33.76%, at MI Wahid Hasyim 34.39% and at MI Ma'arif Bego 43.31%. Before stepping into the cycle II is no reflection on the purpose of evaluating the cycle I and cycle II plan. With the improvements in cycle II expected more efficiently and effectively. The results of supervision and supervision cycle II physical evidence already filled and right on MI Al Islam 86.6%, at 89%, MI Al Ihsan, MI Wahid Hasyim 91.72% and at MI Ma'arif Bego 96.8%. Results of the study showed a rise in MI Al Islam of 71 became 89 with the rise in value or 18%, on MI Al Ihsan from 83 be 93 with the rise in the value of 10 or 10%, at MI Wahid hasyim from 91 be 95 there is a rise in the value of 4 or 4% and on the MI Ma'arif Bego 90 into 98 there is a rise in the value of 8 or 8%. Thus an integrated supervision and supervision on a madrasah that will enhance the value of accreditation can be accredited.